Application Of Oxytocin Massage In Postpartum Midwifery Care At Bina Sehat Primary Clinic - Rahmawati, Isabella (Sahabat Publikasi Kuu, 2024)
Background: The postpartum period begins after the birth of the placenta until the uterine organs return to the pre-pregnancy period which lasts for 42 days. When there are physiological changes during the postpartum period, one of which is lactation, the mother needs continuous support to facilitate the lactation process. Postpartum mothers, especially in mulitipara mothers, will usually experience less breast milk production in the postpartum period. Midwives play a leading role in providing this care in accordance with professional standards, one of which is by providing oxytocin massage services to increase breast milk production to achieve success in exclusive breastfeeding. Objective: Carry out midwifery care during the postpartum period by applying oxytocin massage at Bina Sehat Primary General Clinic. Method: This study uses a descriptive analytical method. Descriptive analytical research is research that seeks to describe a phenomenon, event, or event that occurs currently by focusing on actual problems during the research. Results: The implementation of oxytocin massage during the first postpartum visit began by explaining the meaning, benefits with easy-to-understand language and then the correct way to do oxytocin massage with a direct demonstration to the husband. During the second postpartum visit, the mother said that breast milk production had increased, until the third postpartum visit, the mother said that breast milk production was increasing accompanied by a good nutritional pattern and maternal rest pattern. Conclusion: The application of oxytocin massage is effective in increasing breast milk production.